Effect of fenugreek seeds supplementation on growth performance, digestion coefficient, rumen fermentation and some blood metabolites of Awassi lambs - Anmar A. Majeed Al-Wazeer (Kufa Journal for Veterinary Medical Sciences, 2017)
Twelve Awassi lambs with 5-6 month average 25.13±0.33 kg body weight (BW) were used to investigate the effect of adding graded levels of fenugreek seeds (FS) to the diet on growth performance, nutrient digestibility, rumen fermentation, and some blood metabolites. The lambs were randomly assigned to four treatments (3 lambs per treatment) in a completely randomized design. Treatment diets were control diet without FS 0 g/head/day (FS0), control diet plus 2.5gFS/head/day (FS1), control diet plus 5gFS/head/day (FS2), and control diet plus 7.5gFS /head/day (FS3). Lambs were housed in individual pens and received 600g of concentrate diet once a day with ad libitum choice of rice straw as roughage. Body weight and feed intake were recorded. At the day 42, the digestibility trial was performed for all lambs with same diets. Rumen liquor and blood samples were withdrawn from all the lambs at the last day of digestibility trial. Results showed that increasing level of FS did not improve (P>0.05) feed intake, live weight gain (LWG) and feed conversion ratio (FCR). Fenugreek seeds addition had no effect (P>0.05) on diet digestibility of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF). Results also showed that fenugreek seeds administration did not affect (P>0.05) ruminal pH, ammonia-nitrogen (NH3-N) and total volatile fatty acids (TVFA's) concentration. The NH3-N and TVFA’s concentrations were tended (P>0.05) to decrease as levels of FS increased in the diet. Serum glucose (SG), serum total protein (STP) and serum urea nitrogen (SUN) were not affected also by increasing levels of FS. It can be concluded; supplementation of fenugreek seeds in the diets of fattening Awassi lambs did not improve growth performance, nutrient digestibility and ruminal fermentation without adverse effects on blood metabolites.